Atividade experimental para o ensino de hidrodinâmica: tubo de Venturi - Oliveira, Tatiane de (2019)
This work is aimed at teachers of high school physics and aims to present an experimental approach on topics of hydrodynamics, emphasizing meaningful learning. The proposal is to construct a venturi tube in an easy way and with materials of moderate cost. For its construction was determined accurately the shapes, cutouts and assembly model. Three experimental sets were constructed and subjected to calibration and analysis of their operation. It is still possible to verify the didactic sequence proposed for the application of the educational pro-duct in the classroom, the experimental script presents investigative characteristic because the student will perform the experiment and the teacher will intervene by instigating the logical reasoning through pre existing knowledge. The application of the experiment was carried out for students of the third year of high school in a public educational institution located in the city of Cascavel-PR, the students showed great interest and motivation regarding didactics. Itis concluded that the objective was achieved due to the construction of a venturi tube that matches the materials commercialized in the results obtained.